Syntheses of a radiolabelled CXCR2 antagonist AZD5069 and its major human metabolite. (27th July 2016) - Hickey, Michael J.; Allen, Paul H.; Caffrey, Moya; Hansen, Peter; Kingston, Lee P.; Wilkinson, David J.
Abstract : The CXCR2 antagonist AZD5069 has been synthesized in tritium and carbon‐14‐labelled forms. [ 3 H]AZD5069 was prepared via reductive dehalogenation of an iodinated precursor with tritium gas to provide material with a specific activity of 25.1 Ci/mmol. [ 14 C]AZD5069 was labelled in the pyrimidine ring from [ 14 C]thiourea in an overall radiochemical yield of 18%. In addition, a synthetic route to the major metabolite of AZD5069 was developed. The synthesis of this metabolite was achieved from AZD5069 using a chemoselective Lindgren–Pinnick reaction in order to minimize oxidation of the sulphide group. Abstract : To support the clinical development of a CXCR2 antagonist, the syntheses of tritium and carbon‐14‐labelled AZD5069 are described. A chemoselective Lindgren–Pinnick oxidation to prepare AZD5069 acid metabolite is also presented.